2006
DOI: 10.1002/ange.200600377
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Active and Selective Nanocomposite Catalyst for C7+ Paraffin Isomerization

Abstract: Ein Pt/WO3/Al‐ZrOx‐Nanokomposit wandelt verschiedene Kohlenwasserstoffe bereits bei 150 °C effizient um (siehe Bild, X=Umsatz), ohne dass starkes Cracken oder Verkokung auftreten. Der neuartige Katalysator könnte zur Produktion von Treibstoffen mit hoher Oktanzahl bei niedrigem Arengehalt genutzt werden, da er n‐Alkane mit ausgezeichneter Selektivität in mehrfach verzeigte Isomere überführt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…It is unlikely that H 3 PW 12 O 40 (HPW) would be formed in the zeolite channels by the introduction of tungsten into phosphorus-modified HZSM-5, but some interaction between tungsten and phosphorus species should be expected by doping tungsten species to P/HZSM-5. Furthermore, it has been documented that supported tungsten oxides are good catalysts for isomerization of hydrocarbons, e.g., 1-butene, n -decane and C 7 + paraffins [ 101 105 ]. Considering these properties of tungsten and the anticipated interaction between phosphorus and tungsten, we concluded that doping tungsten into P/HZSM-5 would further promote its catalytic performance for 1-butene cracking.…”
Section: Amorphous Oxide Modified Zeolite Composite Catalystsmentioning
confidence: 99%
“…It is unlikely that H 3 PW 12 O 40 (HPW) would be formed in the zeolite channels by the introduction of tungsten into phosphorus-modified HZSM-5, but some interaction between tungsten and phosphorus species should be expected by doping tungsten species to P/HZSM-5. Furthermore, it has been documented that supported tungsten oxides are good catalysts for isomerization of hydrocarbons, e.g., 1-butene, n -decane and C 7 + paraffins [ 101 105 ]. Considering these properties of tungsten and the anticipated interaction between phosphorus and tungsten, we concluded that doping tungsten into P/HZSM-5 would further promote its catalytic performance for 1-butene cracking.…”
Section: Amorphous Oxide Modified Zeolite Composite Catalystsmentioning
confidence: 99%
“…Among the noble metals, Pt has been shown to considerably increase the selectivity in favour of isomerisation, and is therefore the most suitable metal for the hydroconversion of n-alkanes. [2] Various catalysts have been reported to be active in the hydroisomerisation of C 7 and longer C 7 chain n-alkanes, including materials based on MoO 3 , [13] Pt-WO 3 -ZrO 2 , [4,[14][15][16][17] Al-MCM-41, [18,19] zeolite-supported Pt, [20][21][22][23] and Pt-silicoaluminophosphates (SAPO) materials [8,9,24] as alternatives to the traditional Pt and Re/Al 2 O 3 catalysts. In particular, compared to microporous zeolites, Al-MCM-41 materials have a moderate acidity, and the incorporation of metallic sites into these materials (e.g.…”
Section: Introductionmentioning
confidence: 99%